Anglo-Russian War-Scare and British Occupation of Kŏmundo, 1885–7: The Initial Phase of Globalisation of International Affairs Between Great Powers. Issue 6 (2nd November 2019) - Suzuki, Yu
ABSTRACT: On 15 March 1885, an Anglo-Russian war-scare was unleashed as a result of a skirmish between Russian and Afghan troops, who ran into each other in a region called Penjdeh in Central Asia. Fearing that East Asia might become a battlefield in case an Anglo-Russian war would break out, the British government decided to occupy three islands off the southern coast of Korean peninsula called Kŏmundo, known to the British at that time as Port Hamilton, to improve Britain's strategic foothold in this region. The Penjdeh crisis was the first case in the nineteenth century that an incident in Asia triggered a serious war-scare between the Great Powers. As the European empires continued to expand throughout the nineteenth century, they started to rub their imperial frontiers with each other, and thus it became increasingly possible by the last quarter of the century that events outside of Europe could lead to a serious crisis between them. Yet, despite of its importance, not enough scholarly attention has been given to this incident. This article will address the shortcomings of the existing literature by emphasising the importance of this understudied incident within the broader trend of international history in the late-nineteenth century.